PROBLEMATIKA PENEREPAN KURIKULUM MERDEKA PADA MATA PELAJARAN PAI KELAS 7 DI SMP NEGERI 5 SEMPARUK TAHUN PELAJARAN 2023-2024 - Wardina Wardina; Yayan Ridwan, Ahmad Rathomi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The aim of this research is to analyze and describe: 1) Implementation of the independent curriculum in Islamic Religious Education subjects in class 7 of SMP Negeri 5 Semparuk for the 2023-2024 academic year; 2) Problems with implementing the independent curriculum by Islamic Religious Education subject teachers in class 7 of SMP Negeri 5 Semparuk for the 2023-2024 academic year; 3) Solution to the problem of implementing the independent curriculum by Islamic Religious Education teachers in class 7 of SMP Negeri 5 Semparuk for the 2023-2024 academic year. The approach used is qualitative with a descriptive type. The data source was continued with purposive sampling. The data collection techniques used were observation, interviews and documentation. Meanwhile, data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. Data validity uses source triangulation and member checks. Based on the analysis carried out, the research results show that; 1) the implementation of the independent curriculum in the subject of Islamic Religious Education in class 7 of SMP Negeri 5 Semparuk has gone well with the implementation of the project to strengthen the profile of Pancasila carried out three times a year by raising three themes that have been determined by the government where the profile of Pancasila activities are carried out every two weeks with implementation carried out with preliminary activities, core activities and closing activities. It has gone well where the initial, core and closing activities are as they should be. 2) teacher factors in implementing the independent curriculum in Islamic Religious Education subjects in class 7 of SMP Negeri 5 Semparuk, namely the lack of understanding of Islamic religious education teachers regarding the concept of the independent curriculum, difficulties in compiling teaching modules provided by the government that are modified according to the characteristics of students, as well as when analyzing learning outcomes and developing a flow of learning objectives based on 2 factors, namely internal factors and external factors. 3) Solutions carried out by teachers in facing the problems of implementing the independent curriculum in Islamic Religious Education subjects in class 7 of SMP Negeri 5 Semparuk by actively participating in MGMP activities and socialization of the independent curriculum.